2021
DOI: 10.1039/d1sc03560f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of degradable and chemically recyclable polymers using 4,4-disubstituted five-membered cyclic ketene hemiacetal ester (CKHE) monomers

Abstract: Novel degradable and chemically recyclable polymers were synthesized using five-membered cyclic ketene hemiacetal ester (CKHE) monomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Recently, Goto et al have reported the base degradation of a vinyl polymer of a CKAE to the monomer precursor. 32 Similarly, the base degradation of the vinyl polymer of MBDO was investigated. 10 M aqueous NaOH ([NaOH]/[MBDO units] = 3/1) was added to the solution of the vinyl polymer and the reaction mixture was heated at 70 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Goto et al have reported the base degradation of a vinyl polymer of a CKAE to the monomer precursor. 32 Similarly, the base degradation of the vinyl polymer of MBDO was investigated. 10 M aqueous NaOH ([NaOH]/[MBDO units] = 3/1) was added to the solution of the vinyl polymer and the reaction mixture was heated at 70 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Goto's research team undertook the synthesis of novel CKHE monomers, DMDL and PHDL, which were subsequently co-polymerized with an array of diverse monomers (including vinyl, acrylate, styrene, and acrylonitrile). 56 These endeavors yielded a spectrum of polymer products, characterized by M n values spanning from 30 to 100 kDa (as elucidated in Fig. 13b).…”
Section: Environmental Remediation By Stimuli-cleavable Vinyl Polymermentioning
confidence: 99%
“…Building on previous studies surrounding the degradation of statistical copolymers between vinylic monomers and CKAs, , , the hydrolytic degradation of poly­( 1 - co -MMA) was investigated (Table ). Dissolved in THF, poly­( 1 - co -MMA) could be readily degraded via the addition of NaOH/KOH (1 mol L –1 in H 2 O or MeOH) at room temperature.…”
mentioning
confidence: 99%